A facile solvothermal approach for the synthesis of novel W-doped TiO2 nanoparticles/reduced graphene oxide composites with enhanced photodegradation performance under visible light irradiation. (16th October 2017) - Liu, Xiang; Shi, Yidan; Dong, Yuming; Li, Hexing; Xia, Yongmei; Wang, Haijun
Abstract : W-Doped TiO2 nanoparticles/reduced graphene oxide composites have been synthesized for the first time. The mechanism of their high photocatalytic activity for MB has been identified and discussed. Abstract : High performance W-doped TiO2 nanoparticles/reduced graphene oxide (W-TiO2 /RGO) composites are successfully synthesized through a facile solvothermal method. During this process, TiO2 was doped with W 6+ to generate W-TiO2 nanoparticles, and graphene oxide (GO) was reduced to reduced graphene oxide (RGO), which was uniformly covered with a large number of W-TiO2 nanoparticles. The prepared samples were characterized by various analytical and spectroscopic techniques, including transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), UV-vis diffuse reflectance spectroscopy (UV-vis DRS), specific surface areas (BET) and photoluminescence (PL) spectroscopy. The photocatalytic properties of the prepared samples were evaluated by the photodegradation of methylene blue (MB) as a model pollutant under visible light irradiation. The results confirmed that TiO2 was doped with W 6+ and showed the graphene nature of RGO in W-TiO2 /RGO composites. Additionally, it was found that W 6+ doping could improve the photoresponse of TiO2 nanoparticles under visible light irradiation and graphene could provide conductive electron channels for the separation of electrons and inhibit the recombination of electrons and holes, hence further improving the response of W-TiO2 nanoparticles under visible light irradiation. The W-TiO2 /RGO composites exhibited a much higher photocatalytic activity than mono-modified or non-modified composites and the degradation rate of the W-TiO2 /RGO composites toward MB could reach up to 99.8% in 90 min. No obvious inactivation has been observed in durability experiments. The mechanism of enhanced photocatalytic activity, which arose from the synergistic effect of W 6+ doping and graphene incorporation, was also discussed.